A data-driven framework for assessing soldier performance, health, and survivability. (October 2022) - Mavor, Matthew P.; Gruevski, Kristina M.; Ross, Gwyneth B.; Akhavanfar, Mohammadhossein; Clouthier, Allison L.; Bossi, Linda L.M.; Karakolis, Thomas; Graham, Ryan B.
Abstract: Presented is a framework that uses pattern classification methods to incrementally morph whole-body movement patterns to investigate how personal (sex, military experience, and body mass) and load characteristics affect the survivability tradespace: performance, musculoskeletal health, and susceptibility to enemy action. Sixteen civilians and 12 soldiers performed eight military-based movement patterns under three body-borne loads: ∼5.5 kg, ∼22 kg, and ∼38 kg. Our framework reduces dimensionality using principal component analysis and uses linear discriminant analysis to classify groups and morph movement patterns. Our framework produces morphed whole-body movement patterns that emulate previously published changes to the survivability tradespace caused by body-borne loads. Additionally, we identified that personal characteristics can greatly impact the tradespace when carrying heavy body-borne loads. Using our framework, military leaders can make decisions based on objective information for armour procurement, employment of armour, and battlefield performance, which can positively impact operational readiness and increase overall mission success. Highlights: A novel framework to assess the survivability trade space in soldiers. Morphed movements can represent intermediate movements that were not collected. Movements exportable for MSK modeling, animations, and susceptibility calculations. Personal and body-borne load characteristics affect the survivability tradespace. Objective decision-making tool for armour employment and battlefield performance.